Comparative Life-cycle Assessment of Slurry and Wet Accelerated Carbonation of BOF Slag. (July 2017) - Ghasemi, Sara; Costa, Giulia; Zingaretti, Daniela; Bäbler, Matthäus U.; Baciocchi, Renato
Abstract: This work reports the results of the life cycle assessment (LCA) of two carbonation processes aimed at permanent CO2 storage, employing Basic Oxygen Furnace (BOF) slag from steel manufacturing as alkalinity source. Specifically, the performance of the slurry phase and wet carbonation routes were compared assuming to store the CO2 emitted from a 10 MW conventional natural gas power plant. The LCA was based on the material and energy requirements for each of the involved process steps, i.e. pre-treatment and transport of raw materials, CO2 compression, carbonation, post treatments and management of the obtained products. The slurry and wet route resulted in a net avoided greenhouse warming potential (GWP) of 473 and 384 kg CO2 /MWhel, respectively. Nevertheless, both routes affected the other environmental impact categories. In general, the wet route had approximately two times higher impact than the slurry route, due in particular to the higher material and energy requirements. An exception was the abiotic resource depletion which resulted higher for the slurry route due to greater water requirement with respect to the wet route. The contributions to all mid-point impact categories were mainly due to energy requirements. A sensitivity analysis showed that the environmental impacts are affected by the energy mix and by the transport distance of slags and carbonation products.